Life forms affect beta-diversity patterns of larch forests in China - Wenjing Fang; Qiong Cai; Chengjun Ji; Jiangling Zhu; Zhiyao Tang; Jingyun Fang (Plant Diversity, 2024)
Beta-diversity reflects the spatial changes in community species composition which helps to understand how communities are assembled and biodiversity is formed and maintained. Larch (Larix) forests, which are coniferous forests widely distributed in the mountainous and plateau areas in North and Southwest China, are critical for maintaining the environmental conditions and species diversity. Few studies of larch forests have examined the beta-diversity and its constituent components (species turnover and nestedness-resultant components). Here, we used 483 larch forest plots to determine the total beta-diversity and its components in different life forms (i.e., tree, shrub, and herb) of larch forests in China and to evaluate the main drivers that underlie this beta-diversity. We found that total beta-diversity of larch forests was mainly dependent on the species turnover component. In all life forms, total beta-diversity and the species turnover component increased with increasing geographic, elevational, current climatic, and paleoclimatic distances. In contrast, the nestedness-resultant component decreased across these same distances. Geographic and environmental factors explained 20%–25% of total beta-diversity, 18%–27% of species turnover component, and 4%–16% of nestedness-resultant component. Larch forest types significantly affected total beta-diversity and species turnover component. Taken together, our results indicate that life forms affect beta-diversity patterns of larch forests in China, and that beta-diversity is driven by both niche differentiation and dispersal limitation. Our findings help to greatly understand the mechanisms of community assemblies of larch forests in China.